(untitled) (Research, Society and Development, 2022)
Anti-flu drugs are currently purchased in Brazil without a prescription and represent the second most used class of medication without a prescription from a legally qualified health professional. Self-medication poses risks to patients’ health, and may be related to allergic reactions, cases of intoxication and other drug-related problems. The community pharmacy represents the place of first choice for the treatment of self-limiting problems, where the pharmacist is a key player in the rational use of medicines. Objective: To list the pharmacological and non-pharmacological treatments most used to manage the signs and symptoms of colds and flu; Propose strategies for pharmaceutical management and pharmacotherapeutic follow-up of patients. Methodology: This is a literature review about the rational use and correct management of anti-flu drugs and the role of the clinical pharmacist in the symptomatic treatment of flu and colds. Articles published in LILACS, BIREME, SciELO, Google Scholar, PubMed and MEDLINE were used. Results and discussion: Clinical protocols work as a way to guide health professionals about the correct way to manage patients in health facilities. Pharmacists must adapt to new rules and clinical protocols developed to meet the needs of community pharmacies. Considerations: Respiratory diseases represent a public health problem in both industrialized and non-industrialized countries. The pharmacist is the essential professional in the guidelines, promotion of the rational use of medicines, safety and effectiveness medicines, reduction of self-medication rates and drug-related problems.